Comparison of Grounding Resistance Using Grounding Rod Electrodes with Different Fault Current Types in Podzolic Soil at Prabumulih Substation - Dian Eka Putra; Gamaliel PV Pardede; Falupi Kurniawan; Muhammad Willianto Saputra; Rahmawan Sinaga; Andu Rahmanda; Bambang Rudini; Reza Eka Putra; Muhammad Waladun Salis (Journal of Renewable Energy, Electrical, and Computer Engineering, 2023)
For protection against electric shock in electrical equipment, particularly in control or instrument installations in substation equipment, a quality earthing system is required. The earthing system is also affected by soil resistivity with different soil types. In the equipment grounding system, knowledge of the types of electrodes and the type of soil is required. At the Prabumulih substation, Podzolic soil is required to evaluate the stress distribution that happens in the soil in order to reduce Ground Potential Rise (GPR). In addition to obtaining the economic value of the rod electrode type employed. In this study the resistivity value of the podzolic soil type is very decisive so that the resistivity value of the podzolic soil type at the pre-selection substation land is 150 Î©m.